Production of Membrane Vesicles by Enterococcus faecium Cultured With or Without Subinhibitory Concentrations of Antibiotics and Their Pathological Effects on Epithelial Cells - Kim, Mi Hyun; Kim, Se Yeon; Son, Joo Hee; Kim, Seung Il; Lee, Hayoung; Kim, Shukho; Shin, Minsang; Lee, Je Chul (Frontiers in Cellular and Infection Microbiology, 2019)
Enterococcus faecium is a clinically important pathogen associated with opportunistic infection and multi-drug resistance. E. faecium has been shown to produce membrane vesicles (MVs), but MV production by E. faecium under antibiotic stress conditions and the pathogenic traits thereof have yet to be determined. This study investigated the production of MVs in E. faecium ATCC 700221 cultured with sub-minimum inhibitory concentrations (MICs) of vancomycin or linezolid and determined their pathologic effects on colon epithelial Caco-2 cells. E. faecium ATCC 700221 cultured with 1/2 MIC of vancomycin or linezolid produced 3.0 and 1.5 times more MV proteins than bacteria cultured without antibiotics, respectively. Totals of 438, 461, and 513 proteins were identified in MVs from E. faecium cultured in brain heart infusion broth (MVs/BHI), BHI broth with 1/2 MIC of vancomycin (MVs/VAN), or BHI broth with 1/2 MIC of linezolid (MVs/LIN), respectively. Intact MVs/BHI induced cytotoxicity and the expression of pro-inflammatory cytokine and chemokine genes in Caco-2 cells in a dose-dependent manner, but proteinase K-treated MVs significantly suppressed these pro-inflammatory responses. MVs/LIN were more cytotoxic toward Caco-2 cells than MVs/BHI and MVs/VAN, whereas MVs/VAN stimulated more pro-inflammatory cytokine gene expression in Caco-2 cells than MVs/BHI and MVs/LIN. Overall results indicated that antibiotics modulate the biogenesis and proteomes of MVs in E. faecium at subinhibitory concentrations. MVs produced by E. faecium cultured under antibiotic stress conditions induce strong host cell responses that may contribute to the pathogenesis E. faecium.